Pain in Adults With Cerebral Palsy After Single-Event Multilevel Surgery. (February 2022) - Götze, Marco; Geisbüsch, Andreas; Thielen, Mirjam; Döderlein, Leonhard; Wolf, Sebastian I.; Dreher, Thomas; Putz, Cornelia
Abstract : Objective: The aim of the investigation was to assess the contribution of pain to functional, social, and health-related quality-of-life outcomes in adults with cerebral palsy. Design: This monocentric, prospective study included long-term data for ambulant adults with cerebral palsy and at levels I–III in the Gross Motor Function Classification System who had received orthopedic multilevel surgery in adulthood and in whom preoperative and postoperative three-dimensional gait analysis was conducted, including the Gait Profile Score. A questionnaire including the Visual Analog Scale, Oswestry Disability Index, and European Quality of Life 5 Dimensions 3 Level was analyzed. Results: Twenty-four adults at a mean age of 38.0 yrs were included. Sixteen patients (66.7%) indicated that they experienced pain and 10 patients (41.7%) had pain for more than 6 mos. Overall, 13 patients (54%) experienced both pain and anxiety. There was no correlation of the Gait Profile Score with pain, Gross Motor Function Classification System, and Oswestry Disability Index. The Oswestry Disability Index showed a positive correlation with the Gross Motor Function Classification System ( r = 0.39, P = 0.05) and pain ( r = 0.57, P = 0.004). Conclusions: Pain and anxiety represent relevant comorbidities in adults with cerebral palsy. The occurrence of pain correlates with the Oswestry Disability Index and is higher than in children with cerebral palsy.